PENGARUH PENERAPAN ANGGARAN BERBASIS KINERJA, SISTEM INFORMASI PENGELOLAAN KEUANGAN DAERAH, PENEGAKAN INTEGRITAS DAN NILAI ETIKA, KOMITMEN PADA KOMPETENSI, DAN KEPEMIMPINAN YANG KONDUSIF TERHADAP KINERJA ORGANISASI (Kajian Empiris pada Satuan Kerja Di Pemerintah Kabupaten Sragen) - Sumarjono, Sumarjono (JAB (Jurnal Akuntansi & Bisnis), 2015)
The purpose of this study was to investigate the effect of adoption of Performance Based Budgeting, Financial Management Information System, Enforcement Integrity and Ethical Values, Commitment to Competence, and Leadership Conducive to Organizational Performance in the Government of Sragen. This research is a census, and data collection is done with a questionnaire delivered directly by way of collecting data. Overall 59 samples used in this study. Data analysis using Partial Least Square (PLS) with a statistical program SmartPLS 2.0 M3.These results indicate that the adoption of Performance Based Budgeting, Financial Management Information System, Enforcement Integrity and Ethical Values, Commitment to Competence, and Leadership Conducive have significant positive effect on Organizational Performance.Â Keywords: Performance-Based Budgeting, Financial Management Information System, Enforcement Integrity and Ethical Values, Commitment to Competence, and Leadership Conducive, and Organizational Performance.